Analisis Hubungan antara Kualifikasi Pendidikan, Kompetensi Pedagogik, dan Efikasi Diri dengan Komitmen terhadap Tugas Mudarris di Pesantren Tahfiz Al-Qur’an - Muhamad Sarbini; Unang Wahidin; Agus Mailana; Wulan Anggraeni; Muhamad Chandra (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2025)
In the field of education, particularly in Tahfiz Qur'an pesantren, significant challenges exist regarding the commitment of mudarris (teachers), including issues such as the mismatch between academic qualifications and professional competencies, as well as the increasing demands for pedagogical skills and self-efficacy. Previous research has mainly focused on general schools, with little attention given to the relationship between educational qualifications, pedagogical competence, and self-efficacy among mudarris in Tahfiz Qur'an pesantren. The primary objective of this study is to analyze the impact of educational qualifications, pedagogical competence, and self-efficacy on the task commitment of mudarris at Tahfiz Qur'an pesantren. This study employs a quantitative survey design with 35 mudarris as respondents, and data analysis is conducted using regression techniques. The findings show that educational qualifications do not have a significant effect on task commitment, while both pedagogical competence and self-efficacy have a significant positive impact on mudarris' commitment. It is recommended that pedagogical training programs be made mandatory for mudarris, as academic qualifications alone are insufficient to ensure high levels of task commitment.